All-optical fiber optic coherent amplifier. Issue 1 (December 2018) - Goodarzi, A.; Ghanaatshoar, M.; Mozafari, M.
Abstract A fiber optic-based all-optical amplifier is designed by using the coherent perfect absorption phenomenon. For this purpose, we use a deposited chromium thin layer as an absorbent material on the cross-section of a PM fiber. By placing another fiber in front of the deposited one, we show that by controlling the relative phase between the two counter-propagating beams, total absorbance can be controlled. In the interaction of two beams with unequal intensities, absorption control can be associated with amplification for the weaker beam. By using this mechanism, the effect of an external phase-shifting parameter can be amplified. Furthermore, it is possible to amplify a small signal riding on a CW background through this all-optical procedure.